Properties of the Permeability Transition of Pea Stem Mitochondria - De Col, Valentina; Petrussa, Elisa; Casolo, Valentino; Braidot, Enrico; Lippe, Giovanna; Filippi, Antonio; Peresson, Carlo; Patui, Sonia; Bertolini, Alberto; Giorgio, Valentina; Checchetto, Vanessa; Vianello, Angelo; et al. (Frontiers in Physiology, 2018)
In striking analogy with Saccharomyces cerevisiae, etiolated pea stem mitochondria did not show appreciable Ca2+ uptake. Only treatment with the ionophore ETH129 (which allows electrophoretic Ca2+ equilibration) caused Ca2+ uptake followed by increased inner membrane permeability, membrane depolarization and Ca2+ release. Like the permeability transition (PT) of mammals, yeast and Drosophila, the PT of pea stem mitochondria was stimulated by diamide and phenylarsine oxide and inhibited by Mg-ADP and Mg-ATP, suggesting a common underlying mechanism; yet, the plant PT also displayed distinctive features: (i) as in mammals it was desensitized by cyclosporin A, which does not affect the PT of yeast and Drosophila; (ii) similarly to S. cerevisiae and Drosophila it was inhibited by Pi, which stimulates the PT of mammals; (iii) like in mammals and Drosophila it was sensitized by benzodiazepine 423, which is ineffective in S. cerevisiae; (iv) like what observed in Drosophila it did not mediate swelling and cytochrome c release, which is instead seen in mammals and S. cerevisiae. We find that cyclophilin D, the mitochondrial receptor for cyclosporin A, is present in pea stem mitochondria. These results indicate that the plant PT has unique features and suggest that, as in Drosophila, it may provide pea stem mitochondria with a Ca2+ release channel.